2017
DOI: 10.1155/2017/3028398
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Cephalic Vaginal Delivery Following External Cephalic Version: An Eight-Year Single-Centre Study of 447 Cases

Abstract: Introduction. Our study aims to investigate and evaluate (1) rates of success of ECV for breech presentation at term at the Royal Women's Hospital in comparison to international standards; (2) mode of delivery following ECV; (3) factors influencing success rates of ECV at the Royal Women's Hospital. Methods. An audit of all women who underwent ECV between the years 2007 and 2014 at the Royal Women's Hospital as public patients was completed. Data parameters were collected from paper and electronic patient file… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…A key emphasis since the TBT has been to offer women with a breech presentation external cephalic version. Several large, long-term cohort studies have recently been published to evidence safety, predictors of success, and perinatal outcomes, albeit with an overwhelming focus on high resource settings (Melo et al, 2018;Andrews et al, 2017;Kew et al, 2017;Hutton et al, 2017;Rodgers et al, 2017;Weiniger et al, 2016;Basu et al, 2016). The PREMODA (PREsentation et MODe d'Accouchement) trial used the same criteria and outcome measures as the TBT to address its methodological flaws, but removed the randomised element (Goffinet et al, 2006).…”
Section: College Of Obstetricians and Gynaecologists 2017)mentioning
confidence: 99%
“…A key emphasis since the TBT has been to offer women with a breech presentation external cephalic version. Several large, long-term cohort studies have recently been published to evidence safety, predictors of success, and perinatal outcomes, albeit with an overwhelming focus on high resource settings (Melo et al, 2018;Andrews et al, 2017;Kew et al, 2017;Hutton et al, 2017;Rodgers et al, 2017;Weiniger et al, 2016;Basu et al, 2016). The PREMODA (PREsentation et MODe d'Accouchement) trial used the same criteria and outcome measures as the TBT to address its methodological flaws, but removed the randomised element (Goffinet et al, 2006).…”
Section: College Of Obstetricians and Gynaecologists 2017)mentioning
confidence: 99%
“…These findings are consistent with a study that was reported in Taif, Saudi Arabia that showed 84.1% of the women delivered vaginally and 14.5% of them underwent cesarean section after a successful ECV. It is suggested that ECV should be offered to all women with a breech presentation to minimize the danger of non-cephalic presentation at term and decrease the risk of cesarean section [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that though amnioinfusion and oral hydration could improve the amount of amniotic uid, which could not obviously improve the success rate of ECV [14,40]. Stature of the candidates was the second important indicator to select the candidates during our procedure, because thickness of the abdominal wall directly affect the di culty of grasping of the fetal head and buttocks [41,42]. BMI of the patients ranged from 21.5 to 31.6 in our study, with no difference between the successful and failed group, which might due to the strict screening criteria in our institution.…”
Section: Discussionmentioning
confidence: 99%